Coexistence of Cooperative Models as Structural Answer to Lock-Ins in Diversification Pathways: The Case of the Walloon Dairy Sector - De Herde, Véronique; Baret, Philippe V.; Maréchal, Kevin (Frontiers in Sustainable Food Systems, 2020)
Drawing on an analysis of the Walloon dairy sector, this paper aims at bringing novel insights on the coexistence issue in agrifood transition studies. Whereas most studies explore the coexistence of farm models, our study focuses on value chains, in particular on cooperatives. In the Walloon Region, new dairy cooperatives emerged, as substitute or as complement to the incumbent vertically integrated dairy cooperatives. This paper focusses on the coexistence of dairy cooperative models as enabler of transition towards product diversification. Dairy cooperatives are hybrid actors: economic agents on the market on the one hand, structure of collective agency on the other hand. Williamson’s framework of New Institutional Economics acknowledges that the allocation of resources by cooperatives depends on governance processes and on the wider institutional context in which the cooperatives evolve. Within the broader frame of the Multi-Level Perspective, this approach allows to consider the socio-technical coherence in which the cooperatives evolve, the effects of this coherence on their pathways of development and the complementarity of the cooperative models. This qualitative analysis builds on semi-directed interviews with actors of the Walloon dairy sector. The results outline distinctions between the mainstream dairy cooperatives and the new cooperative models in market approach, definition of milk quality, distribution of added value, governance, and interactions with partners. Both models evolve within a distinct socio-technical coherence, holding, in the case of the mainstream dairy cooperatives, lock-ins to diversification related to the relationship with the farmers-members and the milk they produce in the industrial vertically integrated model. The new cooperative models circumvent these lock-ins through de-integration and externalization of initiatives, remuneration and risk. They allow specific groups of actors –still related or unrelated to the mainstream dairy cooperative - to explore new market pathways in accordance to their potential, and to mutually agree on criteria qualifying milk. This research draws the picture of a possible reconfiguration of the dairy landscape towards a more diversified ecosystem of actors, and invites to consider structures of governance in collective action as a cornerstone-issue, because of their significant role in terms of enablement, co-existence and complementarity throughout the transition process.